2021
DOI: 10.1109/access.2021.3103931
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Machine Learning to Consolidate Critical Success Factors of Lean Six Sigma

Abstract: Lean six sigma (LSS) is a quality improvement phenomenon that has captured the attention of the industry. Aiming at a capability level of 3.4 defects per million opportunities (Six Sigma) and efficient (lean) processes, LSS has been shown to improve business efficiency and customer satisfaction by blending the best methods from Lean and Six Sigma (SS). Many businesses have attempted to implement LSS, but not everyone has succeeded in improving the business processes to achieve expected outcomes. Hence, underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…After exiting the iteration, a particular 6-sigma rule 32 is applied in which the range is between [3,3], where the maximum contrast enhancement is obtained in case of sigma is 3 and the minimum contrast enhancement is obtained in case of sigma is 3 rx(i)={xiQF,false|xifalse|>3ex(μhighfreq+numOfSigma×1L1i=1Lfalse(false|xifalse|μhighfreqfalse)23ex)xi,otherwise,where QF[0,10] and numOfSigma[3,+3]. The numOfSigma is multiplied by the standard deviation of the bins.…”
Section: Proposed Method: Iterative Hementioning
confidence: 99%
See 1 more Smart Citation
“…After exiting the iteration, a particular 6-sigma rule 32 is applied in which the range is between [3,3], where the maximum contrast enhancement is obtained in case of sigma is 3 and the minimum contrast enhancement is obtained in case of sigma is 3 rx(i)={xiQF,false|xifalse|>3ex(μhighfreq+numOfSigma×1L1i=1Lfalse(false|xifalse|μhighfreqfalse)23ex)xi,otherwise,where QF[0,10] and numOfSigma[3,+3]. The numOfSigma is multiplied by the standard deviation of the bins.…”
Section: Proposed Method: Iterative Hementioning
confidence: 99%
“…After exiting the iteration, a particular 6-sigma rule 32 is applied in which the range is between ½−3; 3, where the maximum contrast enhancement is obtained in case of sigma is 3 and the minimum contrast enhancement is obtained in case of sigma is −3 E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 4 ; 1 1 6 ; 3 4 0 r x ðiÞ ¼…”
Section: Introductionmentioning
confidence: 99%
“…2.2 Identification of the key factors to Lean Six Sigma implementation in manufacturing supply chains LSS implementation factors are complex and abundant (Mabrouka et al, 2021), and some of the reported LSS implementation failures are attributed to a poor understanding of cause and effect relationships between the LSS enablers (Perera et al, 2021). The relationship between LSS factors with the supply chain performance in manufacturing industries has been proven significant (Ahmad et al, 2019;Gultom and Wibisono, 2019;Ali et al, 2020).…”
Section: Lss In the Supply Chainmentioning
confidence: 99%
“…LSS implementation factors are complex and abundant (Mabrouka et al. , 2021), and some of the reported LSS implementation failures are attributed to a poor understanding of cause and effect relationships between the LSS enablers (Perera et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To understand the cause-and-effect relationships of factors that make lean six sigma (LSS) effective and to carry out LSS effectively, Perera et al have introduced a new method that uses artificial intelligence and machine learning, specifically natural language processing (NLP). It was stated that this model would contribute to developing final testable models that reveal how LSS elements affect quality performance, customer satisfaction and business performance (Perera et al , 2021). In their study, Elboq et al have used Lean six sigma tools together with deep learning in a textile company.…”
Section: Introductionmentioning
confidence: 99%